2016
DOI: 10.1016/j.otsr.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A numerical model to reproduce squeaking of ceramic-on-ceramic total hip arthroplasty. Influence of design and material

Abstract: Level IV in vitro study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
(56 reference statements)
0
6
2
Order By: Relevance
“…On the other hand, reports of ceramic head fractures with polyethylene liners are negligible 29) . Furthermore, in this study no cases of squeaking were observed in the CoP group, whereas a squeak incidence of up to 20% was reported for CoC bearings in previous studies 30) . Thus, CoP articulation is gradually spotlighted in an effort to reduce several problems in ceramic components.…”
Section: Discussioncontrasting
confidence: 74%
“…On the other hand, reports of ceramic head fractures with polyethylene liners are negligible 29) . Furthermore, in this study no cases of squeaking were observed in the CoP group, whereas a squeak incidence of up to 20% was reported for CoC bearings in previous studies 30) . Thus, CoP articulation is gradually spotlighted in an effort to reduce several problems in ceramic components.…”
Section: Discussioncontrasting
confidence: 74%
“…Most commonly (in half of the in vitro studies), implants were subjected to cycling loading and compression. In [70] a pendulum strike was used and in [56], [68], [71] the implants were rotated manually or with robotic arms to produce squeaking. For in vivo implant assessments, walking was employed in eight out of nine studies, whereas squats/crouches, stair ascent/descent and STS were less popular (Supplemental materials: Table V).…”
Section: Implant Assessmentmentioning
confidence: 99%
“…[28] Furthermore, there were no cases of squeaking in the CoP group in this study, whereas CoC bearings were reported to have a squeak incidence of up to 20% in previous studies. [29] Thus, CoP articulation is gradually spotlighted to reduce several problems in ceramic components. However, the problem with the choice of bearing surface remains controversial, although our results are relatively consistent with those of other previous reports.…”
Section: Discussionmentioning
confidence: 99%